PASSEIO NOTURNO: AN APPLICATION OF GENRE'S THEORY IN THE VIEW OF SEMIOTICS - Duarte, Renata Cristina [UNESP] (Univ Estado Mato Grosso, 2017)
The object analyzed in this paper is the short story Passeio Noturno, by Rubem Fonseca. In this text, we observed the figurativization of a financially successful executive man who belongs to a family that follows the standards of Western society. However, through his personal praxis, this subject has an unexpected performance to the enunciatee-reader, in an attempt to restore some meaning to his meaningless routine. Thereby, our aim is to analyze, based on the French Semiotics and the studies of Jacques Fontanille in his work Semiotique e Litterature (1999), how the textual and discursive properties, responsible for organize the genres, relate into the context of the short story.
Keywords: French semiotics; Genre; Brazilian contemporary short story; Rubem Fonseca